Three clinically relevant findings in lung cancer screening - A. E. Nikolaev; I. A. Blokhin; O. A. Lbova; I. S. Dadakina; V. A. Gombolevskiy; S. P. Morozov (Туберкулез и болезни лёгких)
The Moscow Lung Cancer Screening Project was launched inMoscowin 2017 aimed at selective screening for lung malignant neoplasms using low-dose computed tomography (LDCT) in outpatient settings.The objective of the study: to assess the prevalence of lung cancer predictors, coronary heart disease (CHD), chronic obstructive pulmonary disease (COPD), detected by selective screening for lung cancer by LDCT inMoscow.Subjects and methods. A retrospective study included randomly selected LDCT examinations performed as a part of the Moscow Lung Cancer Screening Program. When re-viewing images and protocols, abnormalities such as foci in the lungs, emphysema, coronary calcium were taken into account.Results. When assessing the prevalence and nature of random findings revealed by screening with LDCT, the following pathologies were found to be the most frequently detected (% of the number of individuals with random findings): coronary artery calcification - 49.3%, thickening of the walls of the bronchi - 34.9%, bronchiectasis - 34.9%, and pulmonary emphysema - 21.6%. In most cases, these findings may have high clinical and/or prognostic significance.Screening for COPD and coronary heart disease will significantly improve the cost-effectiveness and diagnostic value of ongoing ultra-low-dose lung cancer screening.